2022
DOI: 10.1302/2046-3758.118.bjr-2021-0533.r1
|View full text |Cite
|
Sign up to set email alerts
|

The risk of tibial eminence avulsion fracture with bi-unicondylar knee arthroplasty

Abstract: Aims The aim of this study was to determine the risk of tibial eminence avulsion intraoperatively for bi-unicondylar knee arthroplasty (Bi-UKA), with consideration of the effect of implant positioning, overstuffing, and sex, compared to the risk for isolated medial unicondylar knee arthroplasty (UKA-M) and bicruciate-retaining total knee arthroplasty (BCR-TKA). Methods Two experimentally validated finite element models of tibia were implanted with UKA-M, Bi-UKA, and BCR-TKA. Intraoperative loads were applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The monocentric nature of the study with only two implants used was that it may not be possible to extrapolate the results to all patients. The implant dimensions and the influence of positioning on the risk of oversizing or undersizing have not been assessed, which may influence the risk of tibial spine fractures and therefore clinical outcomes [32].…”
Section: Discussionmentioning
confidence: 99%
“…The monocentric nature of the study with only two implants used was that it may not be possible to extrapolate the results to all patients. The implant dimensions and the influence of positioning on the risk of oversizing or undersizing have not been assessed, which may influence the risk of tibial spine fractures and therefore clinical outcomes [32].…”
Section: Discussionmentioning
confidence: 99%
“…118 Stoddart et al suggested that bi-UKA had a similar risk of tibial eminence avulsion fracture to UKA, with a higher risk of fracture when tibial bone density was lower. 119 To conclude, finite element analysis applied to osteoarthritis and joint replacement can provide strong biomechanical evidence for prosthesis design and placement, as well as predicting the outcome of replacement surgery. Therefore, it has a promising future in clinical research.…”
Section: Osteoarthritismentioning
confidence: 99%
“…Stoddart et al . suggested that bi‐UKA had a similar risk of tibial eminence avulsion fracture to UKA, with a higher risk of fracture when tibial bone density was lower 119 …”
Section: Application and Characteristicsmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org condition, since neither were present in the orthoload data (i.e., ACL and PCL for the native, PKA, and CPKA states and PCL only for the TKA state). 3) In native knee compartments, condylar loads were distributed to simulate the effect of the menisci and cartilage, in accordance with a method that has previously been verified (Stoddart et al, 2022) with lab data (Munford et al, 2022). 4) Loading through implants was applied as point load to the implant, in accordance with the previous model validation (Tuncer et al, 2013).…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…CPKA procedures could, in theory, lead to favorable load transfer to bone, as articulating surfaces, ligaments, and bone stock are preserved compared to TKA. However, it is also possible that the regions of bone between implants could lead to unfavorable loading conditions that could, perhaps, accelerate bone loss (through strain shielding) or risk of fracture (through overstraining) (Stoddart et al, 2022).…”
Section: Introductionmentioning
confidence: 99%